2013
DOI: 10.1037/a0029870
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in philosophical dialogue facilitates children’s reasoning about subjectivity.

Abstract: Theories of learning have long emphasized the essential role of social factors in the development of early reasoning abilities. More recently, it has been proposed that the presentation of conflicting perspectives may facilitate young children’s understanding of knowledge claims as potentially subjective—one of many possible representations of the world. This development in epistemological understanding has been proposed to be an important determinant of academic performance and is highly correlated with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…A meta-strategic dimension is discussed with stronger importance to the education field in early years of study in particular, as its understanding allows the instructors and curriculum developers to create a favorable environment for critical thinking efforts as the time passes (Jacobson, 2014). This claim is supported by a practical study undertaken by Walker, Wartenberg and Winner (2013), who reported that there are improved augmentation skills and increased subjectivity perception among seven and eight year olds exposed to a dialogic learning model. Supporting the development theory of critical thinking, Jacobson (2014) suggested that the aforementioned approach supports an assertion that behaviors from particular habits of mind are examples of a meta-strategic dimension, while there is a certain literature gap in understanding whether such an assertion holds for student-level thinking.…”
Section: The Role Of Habits Of Mind For Critical Thinkingsupporting
confidence: 60%
“…A meta-strategic dimension is discussed with stronger importance to the education field in early years of study in particular, as its understanding allows the instructors and curriculum developers to create a favorable environment for critical thinking efforts as the time passes (Jacobson, 2014). This claim is supported by a practical study undertaken by Walker, Wartenberg and Winner (2013), who reported that there are improved augmentation skills and increased subjectivity perception among seven and eight year olds exposed to a dialogic learning model. Supporting the development theory of critical thinking, Jacobson (2014) suggested that the aforementioned approach supports an assertion that behaviors from particular habits of mind are examples of a meta-strategic dimension, while there is a certain literature gap in understanding whether such an assertion holds for student-level thinking.…”
Section: The Role Of Habits Of Mind For Critical Thinkingsupporting
confidence: 60%
“…They noticed that as children aged, they become increasingly able to articulate the difference between the objective and the subjective nature of knowledge and also demonstrated constructivist ways of knowing. In a similar manner, Kuhn, Cheney, and Weinstock (2000) and Walker, Wartenberg, and Winner (2012) used vignettes to examine changes in children's epistemic beliefs but did not use puppets to present these stories.…”
Section: Developmental Approachesmentioning
confidence: 99%
“…To examine epistemic judgments across domains Walker, Wartenberg, and Winner (2012) 7-8-year-olds (USA) To examine the relationships between dialogic pedagogy, skills of argument and epistemic beliefs Interviews Yang and Tsai (2010) 6th-grade students (Taipei)…”
Section: Developmental Approachesmentioning
confidence: 99%
“…Alhough children typically experience difficulty accepting moral disagreements, some interventions have enhanced children's acceptance of moral debate and disagreement. After participating in a discussion-based philosophy class, 2 nd graders argued more effectively and were more likely to shift away from an absolutist level than children in a control group without discussion opportunities (Walker, Wartenberg, & Winner, 2013). This shift was observed only for the domain of moral values.…”
Section: Epistemological Developmentmentioning
confidence: 99%